Development of Unsur Games on the Material of the Periodic System of Elements to Improve Analytical Thinking Skills - Amilatus Sholihah; Rusmini (Jurusan Pendidikan Kimia Universitas Halu Oleo, 2025)
The purpose of this study was to describe the feasibility of the Unsur game media (Susun Unsur) to improve students' analytical thinking skills regarding the topic of the periodic system of elements in terms of validity, practicality, and effectiveness. This research uses the 4-D development model from Thiagarajan, limited to the develop stage and limited trials on 35 students of class XI-11 SMAN 16 Surabaya. The results of the analysis of the feasibility of the Elements game media from the validity aspect seen from 3 criteria, namely content, construct, and graphics, obtained the mode in the very good category. The practicality of the Elements game media seen from activity observations, learning implementation, and student response questionnaires obtained mode in the very good category. The effectiveness of the Element game media is seen from the significant increase in pretest and posttest results of students' analytical thinking skills based on the paired sample t-test statistical test which obtained a significance value of 0.000 (<0.05). Unsur Game Media (Susun Unsur) is declared very feasible and relevant to be developed as an effective learning tool.